Me and My VE, Part 2. (September 2013) - Strater, Laura; Riley, Jennifer; Davis, Fleet; Procci, Katelyn; Bowers, Clint; Beidel, Deborah; Bunnell, Brian; Proaps, Alex; Sankaranarayanan, Ganesh; Li, Baichun; De, Suvranu; Cao, Caroline G. L.
Virtual environments, simulations and serious games are increasingly being employed for research, training, education, evaluation, and various business endeavors. In a redux of a favorite session from HFES 2012, this session will describe and demonstrate some of the diverse uses for virtual environments (VEs) in an alternate demonstration format. The session will begin with demonstrators providing a brief description of their VE, and how they've used it to answer a critical research question or address a unique need, including a video demonstration of the VE in action. After these introductions, all demonstrations will be set up around the room, and session attendees can move around the room for more direct interaction with both the demonstrations and the demonstrators. The objective of the session is to provoke ideas among the attendees for how VEs, simulations and serious games can help address their clinical, research, training, education, evaluation or business needs.